Business cooperation : from theory to practice - Arranz Peña, Nieves, 1962- (Palgrave Macmillan, 2002)
"The authors discuss the economic, organizational, strategic and game theory approaches to cooperation; they then proceed to analyse organization design and cooperation, and the sectors in which cooperation has the greatest relevance, namely in technology and international cooperation." "This book covers the theory and practice of cooperation in all its complex forms, making it an ideal tool for any business considering the pros and cons of carrying out cooperative projects, showing how good cooperation can best be achieved."--BOOK JACKET.